2018
DOI: 10.1002/wsb.896
|View full text |Cite
|
Sign up to set email alerts
|

Seeking efficiency with carnivore survey methods: A case study with elusive martens

Abstract: Obtaining reliable information on species distributions is often the first step in conservation. Distribution information can be used to focus survey efforts to estimate population size and examine drivers of occupancy or other population parameters. We compared detection rates and survey costs for 2 techniques (remote cameras and scent detection teams) used to evaluate distribution of a rare carnivore, Humboldt subspecies of Pacific marten (Martes caurina humboldtensis). We used remote cameras at randomly pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 18 publications
(21 citation statements)
references
References 52 publications
(61 reference statements)
1
19
0
1
Order By: Relevance
“…Nonetheless, recent climate trends involving increased winter temperatures and decreased snowfall in western Washington could reduce available habitat and refugia at high elevations and further threaten the viability of montane marten populations (Dawson et al 2011, Pauli et al 2013, while increasing the extent of available habitat for fishers , Halofsky et al 2017, Suffice et al 2017. Increased surveillance for martens involving more intensive and efficient survey methods, such as scent detection dog teams (Moriarty et al 2018) or over-winter remote camera surveys, would help delineate other areas where martens still occur on the Olympic Peninsula. Further, surveys designed to collect additional genetic samples are essential for evaluating the genetic diversity and demographic characteristics of these potentially threatened marten populations.…”
Section: Discussionmentioning
confidence: 99%
“…Nonetheless, recent climate trends involving increased winter temperatures and decreased snowfall in western Washington could reduce available habitat and refugia at high elevations and further threaten the viability of montane marten populations (Dawson et al 2011, Pauli et al 2013, while increasing the extent of available habitat for fishers , Halofsky et al 2017, Suffice et al 2017. Increased surveillance for martens involving more intensive and efficient survey methods, such as scent detection dog teams (Moriarty et al 2018) or over-winter remote camera surveys, would help delineate other areas where martens still occur on the Olympic Peninsula. Further, surveys designed to collect additional genetic samples are essential for evaluating the genetic diversity and demographic characteristics of these potentially threatened marten populations.…”
Section: Discussionmentioning
confidence: 99%
“…Scent detection teams consisted of a handler and a dog with at least 480 hours of training using lab and simulated field trails (e.g., hidden scats on training boards and in the duff). Detection dog team surveys occurred near recent records of Humboldt marten locations identified using a stratified random design (see [37] for methods). During winter 2015, field teams surveyed 74 randomly located sample units with 2 remote cameras and detected Humboldt martens at 11 locations [26, 37].…”
Section: Methodsmentioning
confidence: 99%
“…Detection dog team surveys occurred near recent records of Humboldt marten locations identified using a stratified random design (see [37] for methods). During winter 2015, field teams surveyed 74 randomly located sample units with 2 remote cameras and detected Humboldt martens at 11 locations [26, 37]. Detection dog teams conducted time- and area-constrained search of 1 km 2 areas centered around all 11 remote camera detections and 11 random remote camera locations without prior Humboldt marten detections.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…We placed bait at this height to keep the bait in the frame while having a substantial portion of foreground visible. Moriarty et al () found no difference in detection of Pacific martens ( Martes caurina ) with bait placed at <0.5 m or 1.4 m. We placed bait north of cameras (with few exceptions) to minimize sun glare in photos (Fig. ).…”
Section: Methodsmentioning
confidence: 99%